Evaluation of e-government (PBT) portal based on usability design / Siti Norbaya Ahmad Najib - Ahmad Najib, Siti Norbaya (2014)
Government portal is one the media that will relate between the government and the citizen. But to make it ease of use to the citizen, the government needs to design the portal that will consist of point of view for the user. In this paper, the research will focus on the design that be implemented in Pihak Berkuasa Tempatan (PBT) portal and find out the issue that's been occurring during using the portal. To collect all the data, there are two methods that have been used, First is by conducting an interview by using one software called Morae which it capture all the movement and face impression during using the three portals. The other method is utilizing a checklist prepared by an expert to go over a certain partial. All the result of this method will be analyzed and discuss the output and the impact of the design to the citizen. The primary aim of this research paper is to identify the usability problem in PBT's Portal and the lack of a design issue. Besides that, evaluate the design factor in current portal and proposed a suitable guideline to the designer is the final result for this research. Even though this research has successfully met the objective, but for future work it will recommend to provide a prototype that consist all the result in finding and act as a guideline to the designer in the future.